2020
DOI: 10.1001/jama.2020.7861
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Parameters in Patients With COVID-19 After Using Noninvasive Ventilation in the Prone Position Outside the Intensive Care Unit

Abstract: as co-investigators (Centre Hospitalier d'Aix-en-Provence, France). Michael Aubourg, MSc, and Pierre Castel, MiM, provided English editing service. None of these individuals received compensation for their contributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
353
1
34

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(422 citation statements)
references
References 4 publications
21
353
1
34
Order By: Relevance
“…Other adjunctive techniques, such as awake-PP, have been widely used in combination with oxygen therapy, NIV or HFNO to correct hypoxemia and avoid the need for invasive MV. [11][12][13][14][15][16] The bene ts of prone positioning in ARDS patients have been well established. By rearrangement of the vertical transpulmonary pressure gradients, prone positioning favors lung recruitment improving V/Q mismatch by decreasing shunt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other adjunctive techniques, such as awake-PP, have been widely used in combination with oxygen therapy, NIV or HFNO to correct hypoxemia and avoid the need for invasive MV. [11][12][13][14][15][16] The bene ts of prone positioning in ARDS patients have been well established. By rearrangement of the vertical transpulmonary pressure gradients, prone positioning favors lung recruitment improving V/Q mismatch by decreasing shunt.…”
Section: Discussionmentioning
confidence: 99%
“…10 Several studies have shown that the combination of awake-PP and HFNO or non-invasive ventilation (NIV) is feasible in patients with severe COVID-19 pneumonia, resulting in an increase in oxygenation or a decrease in the respiratory rate and/or dyspnea. [11][12][13][14][15][16] However, to date, it has not been established whether the combination of HFNO plus awake-PP could prevent the need for invasive MV and decrease the need of ICU resources in COVID-19 patients with ARF. We performed this large multicenter adjusted cohort study to investigate those issues.…”
Section: Introductionmentioning
confidence: 99%
“…Awake proning seems to be bene cial in COVID-19 and should optimally be available to both treatment groups (18). In early May, Italian researchers published data to support the rational and feasibility of combining the Helmet CPAP and prone positioning without reports of harm (19,20). Third was the number of COVID-19 patients requiring intermediate-level care in our institution.…”
Section: Discussionmentioning
confidence: 90%
“…Six of 7 studies were observational (22-28) while 1 study was a prospective feasibility study (29). Six studies (22,23,25,(27)(28)(29) included only adult patients, and 5 were single center (22,25,(27)(28)(29). Three studies included ICU patients alone (22,25,26), 3 included only non-intubated patients outside the ICU setting (27)(28)(29) and one study included both ICU and non-ICU patients (23).…”
Section: Resultsmentioning
confidence: 99%
“…Six studies (22,23,25,(27)(28)(29) included only adult patients, and 5 were single center (22,25,(27)(28)(29). Three studies included ICU patients alone (22,25,26), 3 included only non-intubated patients outside the ICU setting (27)(28)(29) and one study included both ICU and non-ICU patients (23). Six of 7 studies involved a small number of adult patients (22,23,25,(27)(28)(29) (Table 1) Three studies showed improvement in oxygenation with prone position (27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%